Concretization and Blending: Towards a Phenomenological-Cognitive Analysis of Julio Cortázar’s «Continuidad de los parques» (Castilla. Estudios de Literatura, 2018)
In this paper I explore the mutual enlightenment between Ingarden’s phenomenological theory and Dancygier’s cognitive one on the construction of meaning in the literary work. I specifically develop the notion of concretization and analyze the role of imagination in that process, differentiating---in phenomenological terms---its role in linguistic conceptualization from its role in perceptual experience. Then, I show how this distinction may help us understand the cognitive construction of narrative spaces. Finally, I set out to analyze Julio Cortázar’s Continuidad en los parques, showing how the proposed distinction helps us grasp the author’s literary strategy.
Keywords: Concretization; Narrative spaces; Ingarden; Cortázar